Emergence of information infrastructures: a tale of two islands. (1st January 2013) - Schellhammer, Stefan; Reimers, Kai; Klein, Stefan
The healthcare sector is regarded as a potential benefactor of information infrastructures (II), because of its information intensity. Public and private initiatives push towards integrating heterogeneous information and communication systems. This paper contributes to a better understanding of the emergence of II by tracing the evolution of a set of standards. The pharmaceutical distribution industry in the Republic of Ireland and in Australia provides the empirical background for this paper. The successful standardisation in one case and the continuation of proprietary wholesaler systems combined with different mechanisms to provide interoperability in the other serve as starting points for our analysis. By applying standardisation theory we seek to explain the outcomes in each of the cases and propose several extensions to the theory. At the empirical level, our data show that both solutions are viable options and gateways can become functionally equivalent to standards; thereby shaping emerging II in this sector.